(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
The tectonic map shows the structure of Earth Crust of the territory of Republic of Armenia and the main stages of its development. It was worked out basing on the geological map, using geophysical and other data according to the principle "age of folding". The units of tectonic zoning are allocated on the map (folded regions of differrent ages, tectonic zones, subzones, orogenetic depressions, anticlinoriums, synclinoriums), local tectonic structures (anticlinals, synclinals, tectonic depressions, raisings, salt domes, etc.), volcanic centres and formations of different ages. Ruptures faults are dismembered into two groups: deep and intracrustal. The steps of evolution are showed as structure-formation complexes, subcomplexes and stages.